Peran Vital Edukasi dan Pemeriksaan Komposisi Tubuh dalam Pengendalian Sindrom Metabolik pada Populasi Dewasa - Ruslim, Daniel; Santoso, Alexander Halim; Gunaidi, Farell Christian; Bachri, Fiqi Afrizal; Ghina, Andini (Jurnal Pengabdian West Science, 2025)
Metabolic diseases, including hypertension, diabetes, dyslipidemia, and obesity, are becoming increasingly prevalent global health problems. These conditions are commonly associated with central adiposity and low muscle mass, both of which play significant roles in the development of cardiovascular disease and type 2 diabetes mellitus. Body composition measurement is an important method for early screening to detect the risk of metabolic diseases in the adult population. This activity was conducted in Grogol Village, West Jakarta, involving 67 participants. The results showed that most participants had very high total body fat (47 people, 70.15%), with visceral fat levels ranging from normal to high in 46 people (68.19%). Additionally, most participants had low skeletal muscle mass (57 people, 85.07%). Body composition screening proves effective in the early detection of metabolic disease risk, enabling timely lifestyle modifications that can improve quality of life and reduce morbidity and mortality rates. Routine assessments and continuous education are essential to controlling risk factors for metabolic diseases, raising public awareness, and preventing more severe complications.